2008
DOI: 10.1016/j.jcv.2008.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Human rhinoviruses: The cold wars resume

Abstract: The finding of many divergent and previously unrecognized HRV strains has drawn attention and resources back to the most widespread and frequent infectious agent of humans; providing us the chance to seize the advantage in a decades-long cold war.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
95
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 267 publications
4
95
1
Order By: Relevance
“…In contrast to previous reports (Calvo et al 2007, 2008, Cheuk et al 2007, Bonzel et al 2008, we observed that HRV-PIV co-infection (median of 1.5 m.o.) was more …”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to previous reports (Calvo et al 2007, 2008, Cheuk et al 2007, Bonzel et al 2008, we observed that HRV-PIV co-infection (median of 1.5 m.o.) was more …”
Section: Discussioncontrasting
confidence: 99%
“…106(3): 316-321, May 2011 Human rhinovirus (HRV) is typically associated with mild upper respiratory tract infections and exacerbation of asthma in children (Gern & Busse 1999, Manoha et al 2007, Mackay 2008, Kelly & Busse 2008. HRV is a member of the Picornaviridae family and is composed of a nonenveloped particle with a positive-sense single-stranded RNA genome.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] Several real-time, RT-PCR assays have been developed; these have improved the diagnosis of rhinovirus infection over traditional culture methods, which are slow and insensitive. 4 -7 However, only a few published PCR assays have combined reverse transcription and PCR in the same real-time reaction (ie, one-step assay).…”
mentioning
confidence: 99%